New Ln-MOFs based on mixed organic ligands: synthesis, structure and efficient luminescence sensing of the Hg2+ ions in aqueous solutions. Issue 43 (20th October 2021) - Wang, Shu-Ju; Li, Qian; Xiu, Guan-Lin; You, Li-Xin; Ding, Fu; Van Deun, Rik; Dragutan, Ileana; Dragutan, Valerian; Sun, Ya-Guang
Abstract : Four Ln-MOFs (Ln = Ce, Pr, Eu and Tb) based on thiobis(4-methylene-benzoic acid) and 1, 10-phenanthroline were synthesized. The Eu-MOF selectively acts as an excellent luminescence probe for the detection of Hg 2+ ions in waters. Abstract : In view of Hg 2+ ion sensing by luminescence, a series of new, phenanthroline-decorated 3D lanthanide metal organic frameworks (Ln-MOFs) valorising an original combination of four different lanthanides and two organic ligands, i.e. thiobis(4-methylene-benzoic acid) (H2 tmba) and 1, 10-phenanthroline (phen), have been successfully synthesized, namely [Ln4 (tmba)6 (phen)4 ]· m (H2 O)(phen) n [Ln = Ce, m = 3 (1 ); Pr, m = 1 (2 ); Eu, m = 3 (3 ); and Tb, m = 3 (4 )]. Compounds 1–4 were characterised by single-crystal X-ray diffraction, elemental and thermogravimetric analyses, and powder X-ray diffraction. The luminescence properties of complexes 3 and 4 were thoroughly investigated. It is herein proved that compound 3 sensitively and selectively acts as an excellent luminescent probe for the detection of Hg 2+ ions in waters, with a detection limit of 1.00 μM. As additional assets, 3 displays superb stability over a wide pH range (3–12) of the aqueous media, as well as convenient recycling after completion of the detection experiments. The rationale for the observed luminescence quenching effect of mercury might be a strong interaction arising between Hg 2+ ions and the carboxylate oxygen atoms of the tmba 2− ligand. The results open new perspectives for applications in environmental remediation.